If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -2 = 3x + 9 Reorder the terms: -2 + 11x = 3x + 9 Reorder the terms: -2 + 11x = 9 + 3x Solving -2 + 11x = 9 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -2 + 11x + -3x = 9 + 3x + -3x Combine like terms: 11x + -3x = 8x -2 + 8x = 9 + 3x + -3x Combine like terms: 3x + -3x = 0 -2 + 8x = 9 + 0 -2 + 8x = 9 Add '2' to each side of the equation. -2 + 2 + 8x = 9 + 2 Combine like terms: -2 + 2 = 0 0 + 8x = 9 + 2 8x = 9 + 2 Combine like terms: 9 + 2 = 11 8x = 11 Divide each side by '8'. x = 1.375 Simplifying x = 1.375
| y=-2(x-75)+325 | | y=-2(x-60)+220 | | -4z+5=15z+15 | | -4+2x=-12+24x | | (7-8i)(3+4i)= | | -12x+12=7+6x | | 49-2x=13-8x | | -12+12=7+6x | | (6-i)+(-4+4i)= | | 0.5x-(18+x)=3(x+1) | | 1.5x+(3x-1.25)=1 | | y=(x-2)+7 | | 7x-(3x-11)=55 | | 0.35-0.5x=2.65 | | 13-13y=8y-6 | | y=(x-2)+12 | | -4cos(4x)=0 | | 17-5n=11+3n | | 8k+ar=r-2y | | 11-11y=3y-6 | | 3x+x=19+5 | | 19n^2-43n+45=0 | | 2x^2+10x-21=0 | | 9X-17=4X+13 | | 2x^2+10x+37=169 | | Lnx=39.5 | | 9u+2=38 | | f=14+17x-1+x(7) | | 2lnx=ln(9+4x) | | 5e^3x-1=25 | | 3v^2-243=0 | | 2x-10=2x+1 |